Test Method for Ammonia Injection Optimization of SCR Denitrification System Based on CFD Simulation Calculation - Weiqun WANG; Lei ZHANG; Zhijun HUANG; Gaojian FU; Guoqi LI (Zhongguo dianli)
In this paper, a method of simulation calculation with computational fluid dynamics (CFD) is presented to precisely adjust the ammonia injection grid valve by introducing tracer gases into the denitrification system. Through full-scale modeling of the SCR system, and by replacing the original flue gas with the equivalent tracer gases in some ammonia-spraying branches, numerical simulation is conducted for the turbulent flow and multi-component diffusion of the flue gas in the SCR reactor. Then the concentration distribution of tracer gases at the outlet section of the denitrification system are calculated and the corresponding influencing areas of the ammonia-spraying branches at the outlet can be obtained. In this way the operators can be instructed to accurately change the ammonia flow rate by adjusting the opening of each ammonia spray branch so as to make the NOx concentration evenly-distributed at the outlet section of the reactor. Finally, the verification test is carried out on the inlet flue duct of the SCR system of the tower boiler of a 1 000 MW unit. The test results show that this method can improve the efficiency and accuracy of typical tests, and therefore can effectively provide the guidelines for the field ammonia spraying optimization test.